Strategi Pemasaran Produk Melalui Re-branding Es Cokelat pada Kelurahan Menur Pumpungan - Farrel Andhika; Aufa Izzudin Baihaqi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Marketing of product is very important. Marketing can spearhead the number of sales of a product. This study discusses product marketing strategies using rebranding to market the Ice chocolate product in the Menur Pumpungan sub-district. This research aims to determine how effective the rebranding strategy is in increasing Micro, Small, and Medium Enterprises (UMKM) sales in Menur Pumpungan sub-district. This study used a qualitative method by conducting interviews and outreach UMKM under two conditions, before and after rebranding.